Inovasi Pendidikan Indonesia yang Efektif dan Efisien di Era Revolusi Industri 4.0 - Syawang, Sirilus Daniel Agung (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find and understand the strategies needed in shaping / developing effective and efficient Indonesian Education Innovations in the industrial era 4.0. so that the Indonesian nation can prepare human resources who are ready to compete in the world, Indonesian society is prosperous and fully independent. This research uses a qualitative approach, with a case study type method, namely by obtaining data from data sources from scientific journals, scientific articles, e-books taken from the website: Google Scholar, Research Gate, OSC, and journals from certain universities. These data sources were taken by paying attention to the keywords of educational innovation, industrial revolution 4.0, efficient and effective educational innovation. After that, information that is revelant with this research is taken. The result of this research is that there are 5 ways that are strategic values to organize innovation: Basic education, namely family education and focusing on forming good character, nature and work ethic. Making innovations that focus on creating a supportive environment that gives freedom to what students are interested in. Focusing on STEM values in the academic community and based on Pancasila values. Focusing on strengthening the effectiveness of bureaucracy and policies produced by schools and universities. & Focusing on strengthening leadership values